Digital home-lessness: Exploring the links between public Internet access, technological capital, and social inequality - Comi, Matt; Alexander, Perry; Davidson, Drew; Goettlich, Walter A; Smith, Sarah; Staples, William G (Current Sociology, 2024)
Millions of individuals in the United States without a computer or broadband at their residence must rely on public libraries for their Internet access. Drawing on a rich data set of interviews and participant observation at three public libraries, we explore how individuals navigate these complex settings and how they profoundly shape their digital lives and experiences, one we characterize as digital home-lessness. In this article, we identify three themes that characterize the relationship between library computer use and digital home-lessness: lifeline encompasses the diverse set of activities that require computer and broadband access; negotiating access focuses on usability, privacy, and security disadvantages among these users; and risky business concentrates on the multiplicities of insecure Internet and computing practices exacerbated by low technological capital. Our findings push forward literature on the digital divide by illuminating how the experience of digital home-lessness limits social inclusion and reproduces socioeconomic inequality.
Keywords: Digital Divide; Internet Access; Surveillance; Technological Capital; Inequality